Are the welfare losses from imperfect targeting important? - Skoufias, Emmanuel; Coady, David (International Food Policy Research Institute, 2002)
The authors evaluate the size of the welfare losses from using alternative “imperfect” welfare indicators as substitutes for the conventionally preferred consumption indicator. They find that whereas the undercoverage and leakage welfare indices always suggest substantial losses, and the poverty indices suggest substantial losses for the worst performing indices, their preferred welfare index based on standard welfare theory suggests much smaller welfare losses. They also find that one cannot reject the hypothesis that the welfare losses associated with using the better performing alternative indicators are zero. In the case of their preferred welfare index, this reflects the fact that most of the targeting errors, i.e., exclusion and inclusion errors, are highly concentrated around the poverty line so that the differences in welfare weights between those receiving and not receiving the transfers are insufficient to make a difference to the overall welfare impact.